2018
DOI: 10.3332/ecancer.2018.806
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of women regarding breast cancer screening tests in Eastern Iran

Abstract: IntroductionAccording to recent statistics, there has been a rapid growth of breast cancer in developing countries. Thus, early detection is essential. This study is based on the perception of people in the Northeast of Iran regarding breast cancer screening.MethodsIn a cross-sectional study, 1469 women were selected randomly in the period from April to November 2016. The study population consisted of women or their companions referring to outpatient clinics or people in public urban areas who filled out a bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
3
8
0
Order By: Relevance
“…This supports a study that shows that limited resources remain a barrier when it comes to breast cancer screening among women (Anyanwu, Egwuonwu and Ihekwoaba, 2012). Another scholar opined that women in low-income populations are faced with financial incapacitation, which might affect their decision to perform breast cancer screening (Izanloo et al, 2018).…”
Section: Discussion Of Findingssupporting
confidence: 70%
“…This supports a study that shows that limited resources remain a barrier when it comes to breast cancer screening among women (Anyanwu, Egwuonwu and Ihekwoaba, 2012). Another scholar opined that women in low-income populations are faced with financial incapacitation, which might affect their decision to perform breast cancer screening (Izanloo et al, 2018).…”
Section: Discussion Of Findingssupporting
confidence: 70%
“…24,25 Similar observations have previously been made in developed and developing countries, with participants showing poor understanding of major BC risk factors. [27][28][29][30][31][32] Because the majority of female teachers involved in the current study had only goodto-poor knowledge of BC, the results indicate that an educational programme is needed to increase awareness of BC risk factors. Unsatisfactory knowledge of BC risk factors was observed with risk factors such as non-breastfeeding, being overweight, having their first pregnancy after 30 years of age, having menopause after the age of 50 and doing less physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is much higher than knowledge rates for BSE seen in some other studies. 24,[27][28][29][30][31][32][33][34] Nevertheless, Omani women's attitudes towards BSE need improvement, since only 57% of participants indicated practicing BSE. Other studies in Saudi Arabia reported 67.6% of participants had never tried BSE.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with Ahmadian and Samah's (2012) findings in Iran, which revealed that most women were antipathetic to BSE and other screening practices that involved their bodies being touched by and exposed to physicians, so such screening options were habitually ignored by them. Aside from body issues and cultural sensitivity associated with screening measures themselves, many women worldwide are negligent to perform screening because of a "lack of any manifestations of cancer" and the view that "such screening practices were unnecessary" (Izanloo et al, 2018); however, this general passivity is compounded in contexts where fatalism and fear are identified as pervasive obstacles (Smith et al, 2005). A study in China also reported that a lack of time and costs are major reasons for Chinese women refrain from performing mammography testing (Chua et al, 2005).…”
Section: Discussionmentioning
confidence: 99%